2019
DOI: 10.4103/sjmms.sjmms_256_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcomes of sudden cardiac arrest in a university hospital in the Western Region, Saudi Arabia

Abstract: Background:Sudden cardiac arrest (SCA) is a major cause of mortality, yet its epidemiological and outcome data in hospitals from Saudi Arabia are limited.Objectives:This study aimed to evaluate the prevalence, risk factors and outcomes of SCA in a teaching hospital in Jeddah, Saudi Arabia.Methods:This retrospective study included all patients aged ≥18 years with SCA who were resuscitated at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, between January 1 and December 31, 2016. Data were retrieved fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Given the recurrence cases, annual cardiac arrest cases in adults and children are 357900 and 19900 cases respectively in the United States of America (USA) annually (2). Similar studies using Utstein's standards have shown notable changes in occurrence rate of IHCA, so that it is 3.25 out each 1000 cases in the east of Asia (3), There are no exact statistics available in Iran, this index has been reported above some international levels in some Asian countries such as the United Arab Emirates (UAE) and Saudi Arabia (4,5).…”
Section: Introductionmentioning
confidence: 91%
“…Given the recurrence cases, annual cardiac arrest cases in adults and children are 357900 and 19900 cases respectively in the United States of America (USA) annually (2). Similar studies using Utstein's standards have shown notable changes in occurrence rate of IHCA, so that it is 3.25 out each 1000 cases in the east of Asia (3), There are no exact statistics available in Iran, this index has been reported above some international levels in some Asian countries such as the United Arab Emirates (UAE) and Saudi Arabia (4,5).…”
Section: Introductionmentioning
confidence: 91%
“… 19 In Saudi Arabia, out of 429 cases of OHCA, the rates of sudden cardiac arrest were only 3.5% between January and December in 2016 at University Hospital, Western Region, Saudi Arabia. 6 A study obligated at a tertiary care hospital in Riyadh, between 1989 and 1995, showed survival rates of OHCA to hospital discharge was 5.1% for adults and 7.4% for children. 20 Furthermore, mortality rates of OHCA reached 95.8% with low rates of performing CPR by bystanders, according to a study published in 2015, King Khalid University Hospital, Riyadh, Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“… 5 In Saudi Arabia, a prevalence of sudden cardiac arrests (SCAs) number was 7.76 out of 1000 hospital admissions at King Abdulaziz University hospital in 2016. 6 We have no available data for OHCAs in Jeddah.…”
Section: Introductionmentioning
confidence: 99%
“…Penyakit jantung merupakan penyebab utama kematian di dunia, termasuk pada jemaah haji dari Indonesia (Naim et al, 2021). Alzahrani et al (2019) menyebutkan bahwa kasus henti jantung pada usia dewasa sebanyak 7,76 kasus per 1000 orang dewasa di King Abdulaziz University Hospital, Arab Saudi yang merupakan temuan yang lebih tinggi dibandingkan studi lain. Shirah et al (2019) mengungkapkan dalam penelitiannya bahwa seluruh jemaah haji yang mengalami henti jantung di luar rumah sakit dan diberikan RJP, tidak ada satupun yang menunjukkan peningkatan kesadaran secara langsung setelah diberi RJP.…”
Section: Manajemen Pada Penyakit Jantungunclassified